Media Batik Flannel Board untuk Meningkatkan Kreativitas dan Pemahaman Konsep Perbandingan Matematika pada Siswa Sekolah Dasar - Zulkifli, Arif; Sudarti; Trapsilo Prihandono (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
In the current era of independent curriculum learning, the use of media in learning is very relevant to learning the differentiation of each student. This study aims to examine the correlation between the use of learning media in the form of flannel boards, with creative thinking and student learning outcomes The results of this study are the application of batik flannel board media is significant with the results of the creativity of control class students (who are not subjected to variables) is to reach an average score of 66.4 below the completeness number 75 while the results of the creativity of experimental class students (who are subjected to variables) is to reach an average score of 83.5 above the completeness number 75 with the One Sample Kolmogorov-Smirnov Test normality test. While based on the results of the understanding of the control class students reached an average score of 66.4 below the completeness number 75 while the results of the understanding of the experimental class students, namely the class subjected to the batik flannel board media, reached an average score of 83.5 above the completeness number 75 with the One Sample Kolmogorov-Smirnov normality test, with the significance test above 0.05, meaning that the data is normal. In conclusion, the implementation of Batik Flannel Board media can increase creativity and understanding of the concept of Mathematical Comparison material in grade V elementary school students.